Desarrollo de una propuesta para la obtención de cloruro de hierro de grado comercial a partir de licores crippados por oxidación química con cloro a nivel de laboratorio (2018)
The present work shows the development of a proposal to obtain ferric chloride by direct reaction between the ferrous chloride contained in a solution called pickling liquor and chlorine gas. As a first step, the respective characterization of the pickling liquor generated by Emcocables S.A. under the protocol of NTC 3976. Based on the characterization, the theoretical material balance was carried out, in order to estimate the amount of reagents to be used to carry out the chemical reaction and reach the final product. The experimental assembly was carried out and the chemical reaction was carried out, monitoring temperature, chlorine expense and final product formation. Then the experimental material balance was made and the results were compared with the theoretical ones. After carrying out the experimentation and the new characterization of the product obtained, a chemical process proposal was made to obtain the ferric chloride, also evaluating the production costs.